On the mechanisms of superplasticity in Ti–6Al–4V - Alabort, E; Kontis, P; Barba, D; Dragnevski, K; Reed, R (Elsevier, 2016)
Surface observations are used to elucidate the deformation mechanisms responsible for the superplastic effect in Ti–6Al–4V. High-temperature in-situ tests for tensile and shear deformation modes are performed in the scanning electron microscope at temperatures in excess of 700∘ C. Grain boundary sliding is predominant; the micro-mechanics of accommodation are consistent with the dislocation-based Rachinger theory. The volume fraction of β plays a crucial role. For temperatures greater than 850 °C, the α grains remain unaffected; cavitation is minimal and slip bands needed for dislocation-based accommodation are detected in the β phase but are absent in α. At this temperature, grain neighbour switching is observed directly under shear deformation. At a temperature lower than 850∘ C, the β volume fraction is lower and a different mechanism is observed: slip bands in α and cavitation are found to accommodate grain boundary sliding. In addition, an increase in the α phase intragranular dislocation activity triggers the formation of subgrains and dynamic recrystallisation, consistent with the Rachinger dislocation creep effect. For temperatures lower than 700∘ C, superplasticity is absent; classical creep behaviour controlled by dislocation climb persists. A numerical treatment is presented which accounts for the Rachinger effect. The computational results are used to deconvolute the contributions of each of the competing mechanisms to the total strain accumulated.